Lithuania’s Liberation Movement in the West in the Seventh Decade of the 20th Century: A New Generation Came Forth - Banionis, Juozas (Genocidas ir rezistencija, 2009)
This article analyses the intensification of Lithuanian liberation activities in the West in the 1960s. It analyses its causes, what international events were connected with it, how it was reflected in the activities of Lithuanian diaspora organisations, and the relations between diaspora organisations.